2023
DOI: 10.1007/s40279-023-01843-y
|View full text |Cite
|
Sign up to set email alerts
|

Building for the Future: A Systematic Review of the Effects of Eccentric Resistance Training on Measures of Physical Performance in Youth Athletes

Abstract: Background Eccentric resistance training is recognised as an effective stimulus for enhancing measures of muscular strength and power in adult populations; however, its value in youth athletes is currently not well understood. Objective The aim of this systematic review was to critically appraise the effects of eccentric resistance training on measures of physical performance (i.e. muscular strength, jump, sprint and change of direction) in youth athletes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 209 publications
0
3
0
Order By: Relevance
“…However, it is important to highlight that only IPP number 2 includes the acceleration component, which might help to improve the thigh muscles’ robustness to manage the high mechanical loading conditions generated during those locomotive tasks identified as inciting events for sprint-related hamstring and quadriceps muscle injuries. It is worth noting that according to some review articles, which propose some general guidelines for eccentric strength development [ 58 ], the exercise dose within both the mechanics and acceleration components of the IPPs included in this sub-analysis may be insufficient to produce significant improvements in the applied element (i.e., function) of the mechanical capacity of the thigh muscles. Furthermore, in contrast to the fundamental strength exercises commonly integrated into the lower body component of IPPs, the rapid locomotive actions within the mechanics and acceleration components lack a graduated approach in difficulty levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to highlight that only IPP number 2 includes the acceleration component, which might help to improve the thigh muscles’ robustness to manage the high mechanical loading conditions generated during those locomotive tasks identified as inciting events for sprint-related hamstring and quadriceps muscle injuries. It is worth noting that according to some review articles, which propose some general guidelines for eccentric strength development [ 58 ], the exercise dose within both the mechanics and acceleration components of the IPPs included in this sub-analysis may be insufficient to produce significant improvements in the applied element (i.e., function) of the mechanical capacity of the thigh muscles. Furthermore, in contrast to the fundamental strength exercises commonly integrated into the lower body component of IPPs, the rapid locomotive actions within the mechanics and acceleration components lack a graduated approach in difficulty levels.…”
Section: Discussionmentioning
confidence: 99%
“…Inertial loading ensures accommodated resistance, allowing maximal forces to be generated from the first to the last repetition of the set ( Norrbrand, 2008 ). Moreover, properly conducted flywheel exercises may offer a safer and more effective eccentric phase than TRT ( Maroto-Izquierdo et al, 2017b ; Raya-González, Castillo & Beato, 2021 ; Raya-González et al ; Tesch, Fernandez-Gonzalo & Lundberg, 2017 ), leading to improved physical capacity and athletic performance-related adaptations ( Beato & Dello Iacono, 2020 ; Beato et al, 2020 ; Bright et al, 2023 ; De Keijzer, Gonzalez & Beato, 2022 ; Liu et al, 2020 ; Petré, Wernstål & Mattsson, 2018 ). Previous studies have shown that high-load intensity eccentric training is more effective in developing muscle strength and hypertrophy compared to low-load eccentric training ( Dudley et al, 1991 ; English et al, 2014 ; Hakkinen, 1981 ; Norrbrand et al, 2008 ; Norrbrand, Pozzo & Tesch, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…ECC exercise, bearing a large load during the eccentric phase, reportedly induces muscular hypertrophy [ 4 ], increases muscular strength, and improves jump and sprint performance [ 1 , 5 ]. Several recent reviews have clearly shown the effectiveness of training using a flywheel (FW) [ 6 8 ]. Such FW training makes use of the load due to inertia when a disk-shaped weight, an FW, is rotated with acceleration and deceleration, which can repeatedly manifest greater force during the eccentric versus concentric phase [ 9 ].…”
Section: Introductionmentioning
confidence: 99%